2014
DOI: 10.1306/03071413046
|View full text |Cite
|
Sign up to set email alerts
|

Neogene–Quaternary postrift tectonic reactivation of the Bohai Bay Basin, eastern China

Abstract: 5The Bohai Bay Basin, located in the eastern China, is considered to be a Cenozoic rifted basin. 6 The basin is atypical in terms of its Neogene-Quaternary post-rift subsidence history in that it 7 experienced intensive tectonic reactivation, rather than the relative tectonic quiescence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…It is well known that a reactivation of Mesozoic sinistral strike‐slip faults to Cenozoic dextral strike‐slip faults occurred on the TLFZ (Allen et al, , ; Mercier et al, ; Xu et al, ; Xu & Zhu, ). Both our recent detailed investigations (Huang et al, , , , ) and other studies (Hsiao et al, ; Teng et al, ) showed that the Cenozoic dextral strike‐slip motion on the TLFZ initiated at about 40 Ma and was a reactivation of Mesozoic sinistral strike‐slip faults and early Paleogene (65–40 Ma) normal faults. The Cenozoic dextral strike‐slip motion after 40 Ma produced all the flower structures discussed in this study.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…It is well known that a reactivation of Mesozoic sinistral strike‐slip faults to Cenozoic dextral strike‐slip faults occurred on the TLFZ (Allen et al, , ; Mercier et al, ; Xu et al, ; Xu & Zhu, ). Both our recent detailed investigations (Huang et al, , , , ) and other studies (Hsiao et al, ; Teng et al, ) showed that the Cenozoic dextral strike‐slip motion on the TLFZ initiated at about 40 Ma and was a reactivation of Mesozoic sinistral strike‐slip faults and early Paleogene (65–40 Ma) normal faults. The Cenozoic dextral strike‐slip motion after 40 Ma produced all the flower structures discussed in this study.…”
Section: Discussionmentioning
confidence: 48%
“…It is generally agreed that this fault zone experienced sinistral movement during the Mesozoic (Gilder et al, ; Xu & Zhu, ; Xu et al, ; Zhu et al, , ), while during the Cenozoic this fault zone was reactivated as a dextral strike‐slip fault (Allen et al, , ; Hsiao et al, ; Huang et al, , , ; Lin et al, ; Mercier et al, ; Zhu et al, ). The TLFZ runs through the offshore part of the Bohai Bay Basin (Figure b), a Cenozoic rift basin with two evolutionary stages (i.e., a Paleogene synrift stage and a Neogene‐Quaternary postrift stage) (Figure ), and has caused complex tectonic changes to the region including the preferential accumulation of hydrocarbons (Allen et al, , ; Chen & Nabelek, ; Gong et al, ; Huang et al, ). In the Bohai Bay Basin during the Cenozoic, subsequent to a period of extensional deformation (65 Ma to 40 Ma), the TLFZ was reactivated around 40 Ma as a dextral divergent wrench fault (Allen et al, , ; Hsiao et al, ; Huang et al, , , , ; Teng et al, ) (Figure ).…”
Section: Study Area and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…5) revealed the characteristics and differences in fault activity in relation to the tectonic evolution of the BBB. Previous studies (Hou , 1998Huang et al, 2014;Qiu et al, 2015) demonstrated that the Cenozoic tectonic evolution of the BBB occurred in three stages: initial rifting, rifting/subsiding and subsiding (Fig. 3).…”
Section: Phases Of Tectonic Evolutionmentioning
confidence: 90%